Anatomic ankle implant can provide better tibiotalar joint kinematics and loading. (May 2022) - Zhang, Yanwei; Chen, Zhenxian; Zhao, Dahang; Yu, Jian; Ma, Xin; Jin, Zhongmin
Highlights: Two anatomic ankle implants were designed and the kinematics and loads of the tibiotalar joints were evaluated. Anatomic ankle implants significantly improved the kinematic functions and load distribution. The kinematics and load distribution of TAA were not sensitive to the height difference of the medial and lateral talar borders. Abstract: Restoration of ankle kinematic functions is the major objective following total ankle arthroplasty (TAA). However, the clinical results of traditional ankle implants are still unsatisfactory. Anatomic ankle implant may provide better ankle kinematic functions and load distribution. In this study, the biomechanical performances between two potential anatomic ankle implants and a commercial INBONE II implant were compared using a previously developed patient-specific musculoskeletal multibody dynamics model during walking. Furthermore, the effects of the different height differences between the medial and lateral borders on the ankle biomechanics and kinematics were also investigated. Significant improvements in kinematic functions especially in internal-external rotation and inversion-eversion, and in load balance between the medial and lateral contacts of the two anatomic ankle implants were observed, as compared to the INBONE II ankle implant. The design of anatomic ankle implant with the medial peak higher than the lateral peak had better performance in restoring the internal-external rotation and balancing the medial and lateral contact forces. The kinematics and loads were not sensitive to the height difference for the anatomic ankle implant with medial border higher than lateral border. The anatomic articular surface design of artificial ankle implant can provide better tibiotalar joint kinematics and loading, therefore, anatomic ankle implant should be considered in the future implant design and surgical procedures.